2017
DOI: 10.3892/or.2017.5352
|View full text |Cite
|
Sign up to set email alerts
|

Isomahanine induces endoplasmic reticulum stress and simultaneously triggers p38 MAPK-mediated apoptosis and autophagy in multidrug-resistant human oral squamous cell carcinoma cells

Abstract: Advanced oral squamous cell carcinoma (OSCC) is typically aggressive and closely correlated with disease recurrence and poor survival. Multidrug resistance (MDR) is the most critical problem leading to therapeutic failure. Investigation of novel anticancer candidates targeting multidrug-resistant OSCC cells may provide a basis for developing effective strategies for OSCC treatment. In the present study, we investigated the cytotoxic mechanism of a carbazole alkaloid, namely isomahanine, in a multidrug‑resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…Research has shown that cobalt chloride induced autophagy and apoptosis in glioma cells by the p53 pathway (26). Another study revealed that isomahanineinduced autophagy was mediated by p38 mitogen-activated protein kinase (MAPK) signaling pathway in oral squamous cell carcinoma cells (27). Among the various pathways, the AMPK pathway has attracted great attention.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that cobalt chloride induced autophagy and apoptosis in glioma cells by the p53 pathway (26). Another study revealed that isomahanineinduced autophagy was mediated by p38 mitogen-activated protein kinase (MAPK) signaling pathway in oral squamous cell carcinoma cells (27). Among the various pathways, the AMPK pathway has attracted great attention.…”
Section: Discussionmentioning
confidence: 99%
“…In glioma cells, autophagy is induced by cobalt chloride mainly through the p53 pathway (B.-C. Cheng et al, 2017). Another study found that drug-induced MAPK signaling pathway activation might initiate protective autophagy (Utaipan, Athipornchai, Suksamrarn, Chunsrivirot, & Chunglok, 2017). Among various autophagy-related signaling pathways, AMPK, a kinase sensing the energy or nutrient state of cells, has always been a hotspot (Hardie, 2007).…”
mentioning
confidence: 99%
“…CLS-354/WT and CLS-354/DX cell lines were established from human OSCC cell line CLS-354 (CLS Cell line service, GmbH, Eppellheim, Germany) as has been described earlier [23,24]. A monkey kidney epithelial cell line (Vero) was purchased from CLS Cell line service (GmbH, Eppellheim, Germany).…”
Section: Cell Lines and Cell Culture Reagentsmentioning
confidence: 99%
“…After the 24 h-treatment, the spent media were removed, 200 μl of 0.5 mg/ml 3-(4,5dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT; Invitrogen, Life Technologies, USA) solution was added to each well and incubated for 4 h. The formazan crystals were dissolved in DMSO. The absorbance (Abs) was detected at 560 nm and background at 670 nm was subtracted, using a microplate reader [23]. Cell viability was calculated as follows:…”
Section: Cytotoxicity Testmentioning
confidence: 99%
See 1 more Smart Citation